The effect of an electricity tax on aggregate electricity consumption: Evidence from Basel - Benjamin Krebs; Simon Luechinger (Swiss Journal of Economics and Statistics, 2020)
We estimate the effect of an electricity tax on aggregate electricity consumption with the synthetic control method. The tax was introduced in the Swiss city of Basel in 1999 and, together with other tariff changes, increased marginal electricity prices by 5.4-8.0%. We compare the actual and a hypothetical electricity consumption in the years 1999-2006. The latter is a weighted average of electricity consumption in other Swiss cities and captures the hypothetical situation without the tax. We find a statistically insignificant effect of the tax increase of - 2.7 to - 1.9%, which implies a rather small, but not unreasonable, price elasticity of between - 0.5 and - 0.2. Ambiguous effects on average prices and an unfortunate communication by officials may explain why the innovative reform failed to induce a stronger response.
Keywords: H23; Q41; Q48; 330; Electricity tax; Electricity demand; Synthetic control method